2016
DOI: 10.36876/smjhrt.1008
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus-like Particles Consisting of M, G and Prefusion F

Abstract: Several studies have been undertaken to recognize that FI-RSV-induced immunity that triggered the enhanced disease. Studies in mice showed that the FI-RSV vaccine induced high titer but low avidity RSV-specific antibodies that failed to neutralize the virus effectively [21] and induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…These results indicated that zinc chloride has a positive effect against lead acetateinduced Mhc genetic variation. Grüngreiff [37] also reported that zinc is involved in several important biological processes such as cell division, growth, and differentiation, as well as it protects the DNA strand from damage.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that zinc chloride has a positive effect against lead acetateinduced Mhc genetic variation. Grüngreiff [37] also reported that zinc is involved in several important biological processes such as cell division, growth, and differentiation, as well as it protects the DNA strand from damage.…”
Section: Discussionmentioning
confidence: 99%